Investigation of the Photoinduced Deposition Mechanism and Interfacial Properties Related to the Photoelectrochemical Performance of Pb/Cu–Au Bimetallic Nanocrystals. Issue 3 (1st March 2022) - Xu, Haiyan; Sun, Ziwei; Pei, Jing; Sheng, Pengtao; Li, Weili; Li, Songtian
Abstract : Modifying TiO2 with noble metal nanocrystals via photodeposition is an efficient strategy for improving its photoelectrochemical performance. The photodeposition process is still an open question and needs to be further clarified. Herein, we selectively deposited Pb or Cu on Au nanocrystals supported by the branched TiO2 nanostructure to prepare the Au@metal/semiconductor photocatalyst. The results revealed the dependence of the photodeposition mechanism on the type of electrolyte. In an acetic acid–acetate system Pb deposition on Au undergoes both underpotential and overpotential deposition processes, while Cu deposition on Au only displays overpotential deposition behavior. In a nitric acid–nitrate system, however, only underpotential deposition occurs during Pb deposition on Au. Surface microstructure analysis shows that the Cu–Au bimetallic nanocrystals form a typical core/shell structure, while Pb–Au has a Janus structure. The lower ideality factor of Cu/Au–TiO2 than that of Pb/Au–TiO2 indicates an ideal photoelectrode/electrolyte junction for photoelectrochemical reaction, further enhancing carrier transport with a short recombination lifetime of 0.899 ms. Finally, the evaluation of photoelectrochemical performance further confirmed Cu/Au–TiO2 (Au loading amount of about 0.55 mass%) as the optimal photocatalyst, with an efficiency as high as 0.29% or about 1.93 times that of Au–TiO2 (0.15%).